The green haven lifestyle hub, gateway development - Tugano, Rica Jean C.
In 2020, the proposed Metro Manila Rail transit System-7 is expected to be fully-operational. With the introduction of several MRT-7 stations along Commonwealth Avenue to San Jose Bulacan, it is projected that more investors will be encouraged to develop lands in areas where stations are located -- most especially within the 400-800 meter radius. Among the 14 transit stations, Tandang Sora area, shows the most potential for growth -- based on vehicular mobility, pedestrian activity, as well as neighborhood accessibly. In line with this, institutions, like colleges and universities, residential subdivisions, as well as commercial establishments and offices are all visible in the area. This goes to show that there are already potential markets and clients on site. However, currently, the developments on site are not yet maximized -- still, cluster of micro-commercial establishments and street markets are visible, and informal settlements are present, and connections and linkages of immediate surroundings are yet to be established. With this, the proposed Lifestyle Hub and Gateway Development aims to be the pioneer of multi-layered development in the area -- the proposed projects is planned to be a transportation hub, commercial establishments, residential complex and business incubator, all in one. Additionally, because the site is adjacent to UP Diliman, the project also aims to propose another Portal to the University to maximize its potential in terms of accessibility to wider market and client, at the same time, to benefit the university by providing alternative access not only to transportation but also, to alternative housing, and job opportunities.